Hypertrophic information under the view of thuth and post-truth concepts - Sampaio, Denise Braga (2019)
It reflects about the relationships between truth, post-truth and information into the perspective of conceptualizing information hypertrophy in Information Science. It uses as methodology the exploratory, bibliographical research and the conceptual analysis of Walker and Avant, to answer the questions: what is information hypertrophy? What are its characteristics and implications in a so-called informational society? It is supported by the following objectives: to create a concept, for Information Science, of hypertrophic information, and to analyze its relationship with truth and post-truth. The analysis shows that information hypertrophy is closely linked with post-truth and fake news constitution, as noted in fact-checking pages some classifications that tangent with the concept, proving its congruence with the theme.